Probiotic Product Enhances Susceptibility of Mice to Cryptosporidiosis - Oliveira, Bruno C. M. [UNESP]; Widmer, Giovanni (Amer Soc Microbiology, 2018)
Cryptosporidiosis, a leading cause of diarrhea among infants, is caused by apicomplexan parasites classified in the genus Cryptosporidium. The lack of effective drugs is motivating research to develop alternative treatments. With this aim, the impact of probiotics on the course of cryptosporidiosis was investigated. The native intestinal microbiota of specific pathogen-free immunosuppressed mice was initially depleted with orally administered antibiotics. A commercially available probiotic product intended for human consumption was subsequently added to the drinking water. Mice were infected with Cryptosporidium parvum oocysts. On average, mice treated with the probiotic product developed more severe infections. The probiotics significantly altered the fecal microbiota, but no direct association between ingestion of probiotic bacteria and their abundance in fecal microbiota was observed. These results suggest that probiotics indirectly altered the intestinal microenvironment or the intestinal epithelium in a way that favored proliferation of C. parvum. IMPORTANCE The results of our study show that C. parvum responded to changes in the intestinal microenvironment induced by a nutritional supplement. This outcome paves the way for research to identify nutritional interventions aimed at limiting the impact of cryptosporidiosis.
Keywords: Cryptosporidium; cryptosporidiosis; probiotics; fecal microbiota; gut microbiota